Group structures of twistulant matrices over rings - Recillas, H.tapia; Velazco - Velazco, J. Armando (International electronic journal of algebra, 2025)
In this work the algebraic structures of twistulant matrices defined over a ring are studied, with particular attention on their multiplicative structure. It is determined these matrices over a ring are an abelian group and when they are defined over a field the diagonalization of such matrices is considered.